Residual stress distribution in a functionally graded alumina-silicon carbide material - Dancer, C; Achintha, M; Salter, C; Fernie, J; Todd, R (2012)
Functionally graded ceramic structures have a range of potential applications as they enable the exploitation of two ceramic materials with very different properties, such as coefficient of thermal expansion. We report the microstructural investigation of a novel functionally graded structure for alumina and silicon carbide with systematically varied composition. Stresses in the structure have been modelled analytically and by finite-element modelling, and are consistent with fluorescence microscopy measurements of residual stress in the structure. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.